Models of Housing in the Quebec Setting for Individuals With Mental Illness - Dorvil, Henri; Tousignant-Groulx, Julien (Frontiers in Psychiatry, 2019)
The World Health Organization (WHO) defines mental health as « a state of well-being in which every individual realizes his or her own potential, can cope with the normal stresses of live, can work productively and fruitfully, and is able to make a contribution to her or his community » (WHO, 2014). A person’s mental health is shaped by various social, economic, physical and environmental factors, at different stages of life. Risk factors are heavily associated with social inequalities in the domains of employment, housing and education. Theories of social determinants of health (Marmot, 2011; WHO, 2014, 2019) postulate the beneficial effects of factors exterior to medicine (regarding income, housing, education and employment) on the health of individuals and populations. Recognition of the effect of social determinants on the health of vulnerable populations has been at the core of the intervention models and housing services developed by social service professionals in Québec. This article offers a review of housing services provided to psychiatric patients living in the community, over the last 50 years in Quebec. Different models of housing with social support which contribute to the autonomy, the security and the empowerment of psychiatric patients are presented.